Variation and change in Ancient Greek tense, aspect and modality - Bentein, Klaas.; Janse, Mark, 1959-; Soltic, Jorie, 1988- (Amsterdam Studies in Classical Philology, 2017)
In this collective volume edited by Klaas Bentein, Mark Janse, and Jorie Soltic, some of the leading experts in the field explore variation and change in one of the core areas of Ancient Greek grammar: tense, aspect, and modality. The contributors investigate key aspects such as the existence of and competition between linguistic variants, the value of modern linguistic theory for the study of linguistic variation, and the interplay between various dimensions of variation. They focus on various stages of the Greek language (Archaic, Classical, Post-classical, and Byzantine), taking both qualitative and quantitative approaches. By doing so, they offer valuable insights in the multi-faced nature of the Greek verbal system, providing an incentive towards the further study of linguistic variation and change.